3-day intervention program for family members of hikikomori sufferers: A pilot randomized controlled trial - Kubo, Hiroaki; Urata, Hiromi; Sakai, Motohiro; Nonaka, Shunsuke; Kishimoto, Junji; Saito, Kazuhiko; Tateno, Masaru; Kobara, Keiji; Fujisawa, Daisuke; Hashimoto, Naoki; Suzuki, Yuriko; Honda, Yoko; et al. (Frontiers in Psychiatry, 2023)
Backgrounds: Hikikomori, pathological social withdrawal, is becoming a crucial mental health issue in Japan and worldwide. We have developed a 3-day family intervention program for hikikomori sufferers based on Mental Health First Aid (MHFA) and Community Reinforcement and Family Training (CRAFT). This study aims to confirm the effectiveness of the 3-day program by a randomized controlled trial. Methods: This study was registered on the UMIN Clinical Trials Registry (UMIN000037289). Fifteen parents were assigned to the treat as usual (TAU) group (TAU only; Age Mean, 65.6; SD, 7.8), and 14 to the Program group (program + TAU; Age Mean, 67.9; SD, 8.6). This study was discontinued due to the COVID-19 pandemic; the recruitment rate was 36.3% of our target sample size of 80. Results: Perceived skills improved temporally and stigma temporally worsened in the TAU group. Confidence decreased and attitude showed no change in both groups. Aggressive behaviors of hikikomori sufferers were significantly worsened in the Program group; however, no serious domestic violence was reported. In the TAU group, Avoidance and irregular life patterns were improved. Activity levels were worsened in both groups. Two participants (16.7%) in the Program group and one participant (7.7%) in the TAU group reported actual behavioral changes (e.g., utilizing support). Conclusion: We could not draw general conclusions on the effectiveness of the program due to the study discontinuation. Nevertheless, this study indicates the necessity for revision of the program to improve family members’ confidence in engaging with hikikomori sufferers, with safer approaching by families.